2012
DOI: 10.2147/ijgm.s29822
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction and primary antiphospholipid syndrome: a frequent and frightening correlation?

Abstract: Introductionthe correlation between primary antiphospholipid syndrome (APS) and cardiovascular events is well known, but the correlation between APS and sudden death is not clear; it probably correlates with sympathetic alterations of the autonomic system.AimTo compare the autonomic nervous system (ANS) in a group of subjects suffering from APS against that of a control group with no cardiovascular risk factors, matched for age, sex, and body mass index.Subjects and methodsAn equal number (n = 31) of subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…11,21 APS is also associated with an increased risk of cardiovascular disease and mortality. [1][2][3][4][5][6]13,14 The cardiac and neurological manifestations seen in APS occur because of both thrombotic and non-thrombotic mechanisms. The pathogenesis of the non-thrombotic manifestations seen in APS is complex and incompletely understood, but includes antibody-mediated activation of endothelial cells, platelets, monocytes, clotting factors and complement pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,21 APS is also associated with an increased risk of cardiovascular disease and mortality. [1][2][3][4][5][6]13,14 The cardiac and neurological manifestations seen in APS occur because of both thrombotic and non-thrombotic mechanisms. The pathogenesis of the non-thrombotic manifestations seen in APS is complex and incompletely understood, but includes antibody-mediated activation of endothelial cells, platelets, monocytes, clotting factors and complement pathways.…”
Section: Discussionmentioning
confidence: 99%
“…11 Labile hypertension without associated renal disease and autonomic neuropathy were reported in early descriptions of the syndrome, 12 and a recent study by Bilora et al demonstrated abnormalities in cardiovascular autonomic function testing in APS patients without cardiovascular disease, cardiovascular risk factors or other autoimmune disorders. 13 Garcia et al also recently reported impaired aerobic exercise capacity and cardiac autonomic control in APS patients. 14 However, an association between APS and autonomic disorders, such as postural tachycardia syndrome (POTS), neurocardiogenic syncope (NCS) and neurogenic orthostatic hypotension (OH), has not previously been reported.…”
Section: Introductionmentioning
confidence: 90%
“…All the patients gave oral informed consent. The same group was also submitted to the autonomic study for another research protocol already published [7].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, literature about autonomic analysis in these subsets of patients is scarce. However, reduced HRV has been demonstrated in specific cohorts, such as treatment-naïve unselected cancer patients [ 60 ], and autonomic dysfunction in anti-phospholipid syndrome has been shown to closely correlate with thrombophilic state [ 61 ]. As for ANS function, both in vitro and in vivo studies have demonstrated that increased sympathetic activity may trigger a hypercoagulable state per se, either by platelet activation [ 62 ], or by local hemostatic activity increasing vascular resistance [ 63 ].…”
Section: Ans Dysfunction and Ischemic Stroke: Running In Circlesmentioning
confidence: 99%